2022
DOI: 10.3390/nano12091424
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Exposure of Macrophages to Synthetic Amorphous Silica Induces Adaptive Proteome Changes and a Moderate Cell Activation

Abstract: Synthetic amorphous silica (SAS) is a nanomaterial used in a wide variety of applications, including the use as a food additive. Two types of SAS are commonly employed as a powder additive, precipitated silica and fumed silica. Numerous studies have investigated the effects of synthetic amorphous silica on mammalian cells. However, most of them have used an exposure scheme based on a single dose of SAS. In this study, we have used instead a repeated 10-day exposure scheme in an effort to better simulate the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
2
1
0
Order By: Relevance
“…Moreover, reports showing persistent effects of pyrogenic silica showed that a repetitive dosing was needed to induce persistent effects [20], suggesting that counteracting the SAS elimination process was required to induce the adverse effects. Indeed, when a true repeated daily exposure was used on macrophages, a low silicon accumulation was observed [32], in line with the elimination mechanism shown here.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, reports showing persistent effects of pyrogenic silica showed that a repetitive dosing was needed to induce persistent effects [20], suggesting that counteracting the SAS elimination process was required to induce the adverse effects. Indeed, when a true repeated daily exposure was used on macrophages, a low silicon accumulation was observed [32], in line with the elimination mechanism shown here.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it is known that different polarizations of macrophages induce different pHs in the phagosome, with M2 macrophages showing acidic phagosomes and M1 macrophages showing more neutral phagosomes [36]. As the internalization of silica induces the production of pro-inflammatory cytokines such as IL-6 and TNF-a, as shown here, and also the expression of CD38 [32], an M1 polarization marker [37], there is clear evidence that macrophages having internalized silica are skewed towards the M1 state and are thus likely to have non-acidic lysosomes with a high content of oxidizing species. This peculiar environment, together with the presence of proteins in the phagolysosome, which complex a wide variety of ions, may favor the silica degradation observed here.…”
Section: Discussionsupporting
confidence: 63%
“…Although mostly performed on cells derived from tissues other than the intestine, available experiments indicate that ASNP are not markedly cytotoxic towards innate immune cells, although, when directly compared, cells of the macrophage lineage are more sensitive than intestinal epithelial cells [ 36 ]. Most contributions obtained in murine models indicate that ASNP can exert an activating effect on macrophages [ 58 61 ], with pyrogenic ASNP apparently more effective than their precipitated counterparts upon acute exposure [ 59 ]. However, in human macrophages, when used at low, non-toxic doses, ASNP, rather than activate macrophages, can rather modulate their response to natural PAMPs, such as LPS, leading to the intracellular sequestration of membrane receptors and, thus, interfering with cytokine secretion and activation-associated metabolic changes [ 62 , 63 ].…”
Section: Effects On Immune Cells In the Intestine: Activation And Mod...mentioning
confidence: 99%